A manufacturing process of NdFeB magnetic steel

In the manufacturing process of neodymium iron boron magnetic steel, materials such as rare earth metal praseodymium neodymium alloy are mixed with neodymium iron boron magnetic steel scrap magnetic powder, and the aluminized agent components are applied after sintering to form a dense aluminum alloy layer, which solves neodymium The problem of insufficient corrosion resistance of iron-boron magnetic steel has achieved both high corrosion resistance and good magnetic properties.

CN118156016BActive Publication Date: 2025-02-14浙江润泽磁业有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410327016.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-21
Publication Date
2025-02-14
Estimated Expiration
2044-03-21

AI Technical Summary

Technical Problem

The corrosion resistance of existing neodymium iron boron magnets is poor, especially in corrosion environments such as salt spray, their magnetic properties will become weaker, and corrosion resistance needs to be improved.

Method used

The main phase magnetic powder is prepared by mixing rare earth metal praseodymium-neodymium alloy, rare earth metal dysprosium-ferroalloy, boron-ferrobody and other materials, and mixed with the recycled NdFeB magnetic steel scrap magnetic powder at a weight ratio of 3:1, and then passing through the magnetic field orientation pressure After the model, the aluminized agent component is applied to the surface of the sintering blank to form a dense aluminum alloy layer to improve corrosion resistance.

Benefits of technology

The corrosion resistance of neodymium-ferrous boron magnets is significantly improved, while maintaining good magnetic properties, making the prepared neodymium-ferrous boron magnets have excellent market application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of permanent magnetic materials, and in particular to a manufacturing process of NdFeB magnets. The invention firstly uses rare earth metal praseodymium-neodymium alloy, rare earth metal dysprosium-iron alloy, ferroboron, pure iron, ferroniobium, aluminum powder, pure gallium, pure copper and pure zirconium as main phase components, and prepares main phase magnetic powder through hydrogen crushing and air flow grinding process. Then, the main phase magnetic powder is mixed with waste magnetic powder prepared by recycling NdFeB magnet waste, so that the production cost can be reduced on the basis of improving the magnetic properties of NdFeB magnets. Secondly, an aluminizing agent component is coated on the surface of a sintered blank, and a dense aluminum alloy layer metallurgically bonded with a matrix can be formed on the surface of the sintered blank after surface hot aluminizing, so that the corrosion resistance of the prepared NdFeB magnet can be improved, and the good magnetic properties of the NdFeB magnet can be maintained to a certain extent, so that the NdFeB magnets prepared by the invention have excellent market application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of permanent magnetic materials, and in particular to a manufacturing process of NdFeB magnetic steel. Background Art

[0002] NdFeB magnets are an important type of permanent magnetic material. Due to their excellent magnetic properties, such as high magnetic energy product, high coercive force and good thermal stability, they are widely used in electronics, power machinery, medical equipment, automotive industry, aerospace and other fields. In the production process of sintered NdFeB magnets, NdFeB castings are generally hydrogen-crushed and air-flow-milled to obtain powders with qualified particle size and uniform distribution, which enter the subsequent molding and sintering process, and then qualified NdFeB magnets are prepared. The corrosion resistance of existing NdFeB magnets is poor, and its magnetism will be weakened in corrosive environments such as salt spray. Therefore, it is necessary to improve the corrosion resistance of NdFeB magnets in the prior art.

[0003] At present, there is a method for preparing ultra-high coercivity sintered NdFeB magnets, which combines the advantages of the traditional dual alloy method and the single alloy grain boundary addition method, and provides a method that is simple to operate and suitable for mass production of ultra-high coercivity and high remanence sintered NdFeB magnets. However, the NdFeB magnets prepared by this method still cannot reach the ideal state in terms of corrosion resistance, and its corrosion resistance needs to be improved on this basis. Summary of the invention

[0004] In view of the above analysis, an embodiment of the present invention aims to provide a manufacturing process of NdFeB magnets, which can effectively solve the problem of poor corrosion resistance of NdFeB magnets in the prior art.

[0005] The present invention provides a manufacturing process of NdFeB magnetic steel, the manufacturing process comprising the following steps:

[0006] Step 1: preparing a main phase component by mixing rare earth metal praseodymium-neodymium alloy, rare earth metal dysprosium-iron alloy, ferroboron, pure iron, ferroniobium, aluminum powder, pure gallium, pure copper and pure zirconium;

[0007] Step 2: The main phase components are cleaned and dried, and then subjected to hydrogen crushing and air flow milling processes to prepare the main phase magnetic powder, and the NdFeB magnetic steel waste is recycled and processed to prepare the waste magnetic powder;

[0008] Step 3: mixing the main phase magnetic powder and the scrap magnetic powder in a weight ratio of 3:1, and then pressing the mixed magnetic field oriented magnetic powder into a green compact;

[0009] Step 4: placing the green body in a vacuum sintering furnace and sintering at 1030-1080° C. for 180 min, tempering at 850-920° C. for 150 min, and then tempering at 460-550° C. for 180 min, the result is recorded as a sintered body;

[0010] Step 5: Mix aluminum powder and anhydrous ethanol to prepare an aluminizing agent component, then evenly apply the aluminizing agent component on the surface of the sintered blank, and obtain NdFeB magnet after sintering.

[0011] Furthermore, the main phase components in step 1 are rare earth metal praseodymium-neodymium alloy with a purity of more than 99%, rare earth metal dysprosium-iron alloy with a purity of more than 99%, ferroboron with a purity of more than 99%, pure iron with a purity of more than 99%, ferroniobium with a purity of more than 99%, aluminum powder with a diameter of D5-D20 mm, gallium with a purity of more than 99%, copper with a purity of more than 99% and zirconium with a purity of more than 99% in a weight ratio of 30:15:12:15:8:0.3:0.2:0.5:0.7.

[0012] Furthermore, the specific operation of cleaning and drying in step 2 is: pouring the main phase component into dilute hydrochloric acid with a mass concentration of 5% and stirring for cleaning, stirring at a stirring speed of 100-200 r / min for 1-2 minutes, filtering to remove the filtrate and washing with distilled water for 3-5 times, and then placing it under 35°C hot air to dry.

[0013] Furthermore, the conditions for hydrogen crushing in step 2 are: hydrogen absorption pressure 220 kpa, hydrogen absorption time 2 h, dehydrogenation temperature 823 K, dehydrogenation time 6 h, the grinding gas pressure of the air flow mill process in step 2 is 0.45~0.6 Mpa, and the powder particle size is 3.1~3.3 μm.

[0014] Furthermore, the preparation steps of the waste magnetic powder in step 2 are:

[0015] Step 1: Soak the NdFeB magnet waste in trichloroethylene at 60°C for 5-6 minutes, then perform ultrasonic treatment at a frequency of 21-22kHz for 2-3 minutes and filter to remove trichloroethylene;

[0016] Step 2: Soak the NdFeB magnet scrap treated in step 1 in a 20% hydrochloric acid solution and a 20% nitric acid solution in sequence, with a uniform soaking time of 20 seconds, filter out the filtrate and place in distilled water at 34-40°C, perform ultrasonic treatment at a frequency of 22-23kHz for 2-3 minutes, filter out the filtrate and blow dry with hot air at 38-40°C;

[0017] Step 3: The NdFeB magnet scrap processed in step 2 is processed by hydrogen crushing and air flow grinding to obtain scrap magnetic powder.

[0018] Furthermore, the conditions for hydrogen crushing in step three are: hydrogen absorption pressure 220 kpa, hydrogen absorption time 2 h, dehydrogenation temperature 823 K, dehydrogenation time 6 h, the grinding gas pressure of the air flow mill process in step three is 0.45~0.6 Mpa, and the powder particle size is 2.8~3.1 μm.

[0019] Furthermore, the orientation magnetic field conditions of the magnetic field orientation molding in step 3 are: the ambient oxygen content is less than 0.003% under argon protection, the orientation magnetic field is 2.0T, and the pressure is 5MPa. The molding operation of the magnetic field orientation molding in step 3 is: static pressing at a pressure of 200MPa to a density of 6.5g / cm 2 of the green body.

[0020] Furthermore, the two tempering treatments in step 4 are both below 5×10 -3 Pa under vacuum conditions.

[0021] Furthermore, the preparation method of the aluminizing agent component in step 5 is: dispersing aluminum powder in anhydrous ethanol at a weight ratio of 4:11, and ultrasonically dispersing at a frequency of 25-28 kHz for 5-8 minutes to obtain the aluminizing agent component.

[0022] Furthermore, the specific operation of the sintering treatment in step 5 is: firstly heat infiltration at a temperature of 700° C. for 1 hour, and then tempering at a temperature of 500° C. for 2 hours.

[0023] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects: the present invention first uses rare earth metal praseodymium-neodymium alloy, rare earth metal dysprosium-iron alloy, ferroboron, pure iron, ferroniobium, aluminum powder, pure gallium, pure copper and pure zirconium as main phase components, and prepares main phase magnetic powder through hydrogen crushing and air flow grinding process, and then mixes the main phase magnetic powder with waste magnetic powder prepared after recycling of NdFeB magnet waste, thereby reducing the production cost on the basis of improving the magnetic properties of NdFeB magnet; secondly, the aluminizing agent component is coated on the surface of the sintered blank, and after surface hot aluminizing, a dense aluminum alloy layer metallurgically bonded with the matrix can be formed on the surface of the sintered blank, thereby improving the corrosion resistance of the prepared NdFeB magnet, maintaining the good magnetic properties of the NdFeB magnet to a certain extent, so that the NdFeB magnet prepared by the present invention has an excellent market application prospect.

[0024] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be achieved and obtained through the contents particularly pointed out in the description. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] The present invention will be further described below in conjunction with the embodiments.

[0027] Example 1

[0028] A manufacturing process of a NdFeB magnet in this embodiment includes the following steps:

[0029] Step 1: preparing a main phase component by mixing rare earth metal praseodymium-neodymium alloy, rare earth metal dysprosium-iron alloy, ferroboron, pure iron, ferroniobium, aluminum powder, pure gallium, pure copper and pure zirconium;

[0030] Step 2: The main phase components are cleaned and dried, and then subjected to hydrogen crushing and air flow milling processes to prepare the main phase magnetic powder, and the NdFeB magnetic steel waste is recycled and processed to prepare the waste magnetic powder;

[0031] Step 3: mixing the main phase magnetic powder and the scrap magnetic powder in a weight ratio of 3:1, and then pressing the mixed magnetic field oriented magnetic powder into a green compact;

[0032] Step 4: placing the green body in a vacuum sintering furnace and sintering at 1030° C. for 180 min, tempering at 850° C. for 150 min, and then tempering at 460° C. for 180 min, the result is recorded as a sintered body;

[0033] Step 5: Mix aluminum powder and anhydrous ethanol to prepare an aluminizing agent component, then evenly apply the aluminizing agent component on the surface of the sintered blank, and obtain NdFeB magnet after sintering.

[0034] The main phase components in step 1 are rare earth metal praseodymium-neodymium alloy with a purity of more than 99%, rare earth metal dysprosium-iron alloy with a purity of more than 99%, ferroboron with a purity of more than 99%, pure iron with a purity of more than 99%, ferroniobium with a purity of more than 99%, aluminum powder with a diameter of D5mm, gallium with a purity of more than 99%, copper with a purity of more than 99% and zirconium with a purity of more than 99% in a weight ratio of 30:15:12:15:8:0.3:0.2:0.5:0.7.

[0035] The specific operation of cleaning and drying in step 2 is: pour the main phase component into dilute hydrochloric acid with a mass concentration of 5% and stir and clean it at a stirring speed of 100r / min for 1 minute, filter and remove the filtrate, wash it with distilled water for 3 times, and then place it under hot air at 35°C to dry it.

[0036] The conditions for hydrogen crushing in step 2 are: hydrogen absorption pressure 220 kpa, hydrogen absorption time 2 h, dehydrogenation temperature 823 K, dehydrogenation time 6 h, grinding gas pressure of the air flow mill process in step 2 0.45 MPa, powder particle size 3.1 μm.

[0037] The preparation steps of waste magnetic powder in step 2 are:

[0038] Step 1: Soak the NdFeB magnet waste in trichloroethylene at 60°C for 5 minutes, then perform ultrasonic treatment at a frequency of 21kHz for 2 minutes and then filter to remove the trichloroethylene;

[0039] Step 2, soak the NdFeB magnet scrap treated in step 1 in a 20% hydrochloric acid solution and a 20% nitric acid solution in sequence, with a uniform soaking time of 20 seconds, filter out the filtrate and place in 34°C distilled water, perform ultrasonic treatment at a frequency of 22kHz for 2 minutes, filter out the filtrate and blow dry with hot air at 38°C;

[0040] Step 3: The NdFeB magnet waste material processed in step 2 is processed by hydrogen crushing and air flow grinding to obtain waste magnetic powder.

[0041] The conditions for hydrogen crushing in step three are: hydrogen absorption pressure 220 kpa, hydrogen absorption time 2 h, dehydrogenation temperature 823 K, dehydrogenation time 6 h, the grinding gas pressure of the air flow mill process in step three is 0.45 MPa, and the powder particle size is 2.8 μm.

[0042] The orientation magnetic field conditions of the magnetic field orientation molding in step 3 are: the ambient oxygen content is less than 0.003% under argon protection, the orientation magnetic field is 2.0T, and the pressure is 5MPa. The molding operation of the magnetic field orientation molding in step 3 is: static pressing at a pressure of 200MPa to a density of 6.5g / cm 2 of the green body.

[0043] In step 4, both tempering treatments were performed at a temperature below 5×10 -3 Pa under vacuum conditions.

[0044] The preparation method of the aluminizing agent component in step 5 is: disperse aluminum powder in anhydrous ethanol at a weight ratio of 4:11, and ultrasonically disperse it at a frequency of 25 kHz for 5 minutes to obtain the aluminizing agent component.

[0045] The specific operation of the sintering treatment in step 5 is: first, heat infiltration at a temperature of 700° C. for 1 hour, and then tempering at a temperature of 500° C. for 2 hours.

[0046] Example 2

[0047] A manufacturing process of a NdFeB magnet in this embodiment includes the following steps:

[0048] Step 1: preparing a main phase component by mixing rare earth metal praseodymium-neodymium alloy, rare earth metal dysprosium-iron alloy, ferroboron, pure iron, ferroniobium, aluminum powder, pure gallium, pure copper and pure zirconium;

[0049] Step 2: The main phase components are cleaned and dried, and then subjected to hydrogen crushing and air flow milling processes to prepare the main phase magnetic powder, and the NdFeB magnetic steel waste is recycled and processed to prepare the waste magnetic powder;

[0050] Step 3: mixing the main phase magnetic powder and the scrap magnetic powder in a weight ratio of 3:1, and then pressing the mixed magnetic field oriented magnetic powder into a green compact;

[0051] Step 4: placing the green body in a vacuum sintering furnace and sintering at 1080° C. for 180 min, tempering at 920° C. for 150 min, and then tempering at 550° C. for 180 min, the result is recorded as a sintered body;

[0052] Step 5: Mix aluminum powder and anhydrous ethanol to prepare an aluminizing agent component, then evenly apply the aluminizing agent component on the surface of the sintered blank, and obtain NdFeB magnet after sintering.

[0053] The main phase components in step 1 are rare earth metal praseodymium-neodymium alloy with a purity of more than 99%, rare earth metal dysprosium-iron alloy with a purity of more than 99%, ferroboron with a purity of more than 99%, pure iron with a purity of more than 99%, ferroniobium with a purity of more than 99%, aluminum powder with a diameter of D20mm, gallium with a purity of more than 99%, copper with a purity of more than 99% and zirconium with a purity of more than 99% in a weight ratio of 30:15:12:15:8:0.3:0.2:0.5:0.7.

[0054] The specific operation of cleaning and drying in step 2 is: pour the main phase component into dilute hydrochloric acid with a mass concentration of 5% and stir and clean it at a stirring speed of 200r / min for 2 minutes, filter and remove the filtrate, wash it with distilled water for 5 times, and then place it under hot air at 35°C to dry it.

[0055] The conditions for hydrogen crushing in step 2 are: hydrogen absorption pressure 220 kpa, hydrogen absorption time 2 h, dehydrogenation temperature 823 K, dehydrogenation time 6 h, grinding gas pressure of the air flow mill process in step 2 0.6 MPa, powder particle size 3.3 μm.

[0056] The preparation steps of waste magnetic powder in step 2 are:

[0057] Step 1: Soak the NdFeB magnet scrap in trichloroethylene at 60°C for 6 minutes, then perform ultrasonic treatment at a frequency of 22kHz for 3 minutes and filter to remove trichloroethylene;

[0058] Step 2: Soak the NdFeB magnet scrap treated in step 1 in a 20% hydrochloric acid solution and a 20% nitric acid solution in sequence, with a uniform soaking time of 20 seconds, filter out the filtrate and place in 40°C distilled water, perform ultrasonic treatment at a frequency of 23kHz for 3 minutes, filter out the filtrate and blow dry with hot air at 40°C;

[0059] Step 3: The NdFeB magnet waste material processed in step 2 is processed by hydrogen crushing and air flow grinding to obtain waste magnetic powder.

[0060] The conditions for hydrogen crushing in step three are: hydrogen absorption pressure 220 kpa, hydrogen absorption time 2 h, dehydrogenation temperature 823 K, dehydrogenation time 6 h, the grinding gas pressure of the air flow mill process in step three is 0.6 MPa, and the powder particle size is 3.1 μm.

[0061] The orientation magnetic field conditions of the magnetic field orientation molding in step 3 are: the ambient oxygen content is less than 0.003% under argon protection, the orientation magnetic field is 2.0T, and the pressure is 5MPa. The molding operation of the magnetic field orientation molding in step 3 is: static pressing at a pressure of 200MPa to a density of 6.5g / cm 2 of the green body.

[0062] In step 4, both tempering treatments were performed at a temperature below 5×10 -3 Pa under vacuum conditions.

[0063] The preparation method of the aluminizing agent component in step 5 is: disperse aluminum powder in anhydrous ethanol at a weight ratio of 4:11, and ultrasonically disperse it at a frequency of 28 kHz for 8 minutes to obtain the aluminizing agent component.

[0064] The specific operation of the sintering treatment in step 5 is: first, heat infiltration at a temperature of 700° C. for 1 hour, and then tempering at a temperature of 500° C. for 2 hours.

[0065] Example 3

[0066] A manufacturing process of a NdFeB magnet in this embodiment includes the following steps:

[0067] Step 1: preparing a main phase component by mixing rare earth metal praseodymium-neodymium alloy, rare earth metal dysprosium-iron alloy, ferroboron, pure iron, ferroniobium, aluminum powder, pure gallium, pure copper and pure zirconium;

[0068] Step 2: The main phase components are cleaned and dried, and then subjected to hydrogen crushing and air flow milling processes to prepare the main phase magnetic powder, and the NdFeB magnetic steel waste is recycled and processed to prepare the waste magnetic powder;

[0069] Step 3: mixing the main phase magnetic powder and the scrap magnetic powder in a weight ratio of 3:1, and then pressing the mixed magnetic field oriented magnetic powder into a green compact;

[0070] Step 4, placing the green body in a vacuum sintering furnace and sintering at 1050° C. for 180 min, tempering at 890° C. for 150 min, and then tempering at 500° C. for 180 min, the result is recorded as a sintered body;

[0071] Step 5: Mix aluminum powder and anhydrous ethanol to prepare an aluminizing agent component, then evenly apply the aluminizing agent component on the surface of the sintered blank, and obtain NdFeB magnet after sintering.

[0072] The main phase components in step 1 are rare earth metal praseodymium-neodymium alloy with a purity of more than 99%, rare earth metal dysprosium-iron alloy with a purity of more than 99%, ferroboron with a purity of more than 99%, pure iron with a purity of more than 99%, ferroniobium with a purity of more than 99%, aluminum powder with a diameter of D15mm, gallium with a purity of more than 99%, copper with a purity of more than 99% and zirconium with a purity of more than 99% in a weight ratio of 30:15:12:15:8:0.3:0.2:0.5:0.7.

[0073] The specific operation of cleaning and drying in step 2 is: pour the main phase component into dilute hydrochloric acid with a mass concentration of 5% and stir and clean it at a stirring speed of 200r / min for 2 minutes, filter and remove the filtrate, wash it with distilled water for 4 times, and then place it under hot air at 35°C to dry it.

[0074] The conditions for hydrogen crushing in step 2 are: hydrogen absorption pressure 220 kpa, hydrogen absorption time 2 h, dehydrogenation temperature 823 K, dehydrogenation time 6 h, grinding gas pressure of the air flow mill process in step 2 is 0.52 MPa, and the powder particle size is 3.2 μm.

[0075] The preparation steps of waste magnetic powder in step 2 are:

[0076] Step 1: Soak the NdFeB magnet scrap in trichloroethylene at 60°C for 6 minutes, then perform ultrasonic treatment at a frequency of 22kHz for 2 minutes and filter to remove trichloroethylene;

[0077] Step 2: Soak the NdFeB magnet scrap treated in step 1 in a 20% hydrochloric acid solution and a 20% nitric acid solution in sequence, with a uniform soaking time of 20 seconds, filter out the filtrate and place in 37°C distilled water, perform ultrasonic treatment at a frequency of 23kHz for 2 minutes, filter out the filtrate and blow dry with hot air at 39°C;

[0078] Step 3: The NdFeB magnet scrap processed in step 2 is processed by hydrogen crushing and air flow grinding to obtain scrap magnetic powder.

[0079] The conditions for hydrogen crushing in step three are: hydrogen absorption pressure 220 kpa, hydrogen absorption time 2 h, dehydrogenation temperature 823 K, dehydrogenation time 6 h, the grinding gas pressure of the air flow mill process in step three is 0.52 MPa, and the powder particle size is 2.9 μm.

[0080] The orientation magnetic field conditions of the magnetic field orientation molding in step 3 are: the ambient oxygen content is less than 0.003% under argon protection, the orientation magnetic field is 2.0T, and the pressure is 5MPa. The molding operation of the magnetic field orientation molding in step 3 is: static pressing at a pressure of 200MPa to a density of 6.5g / cm 2 of the green body.

[0081] In step 4, both tempering treatments were performed at a temperature below 5×10 -3 Pa under vacuum conditions.

[0082] The preparation method of the aluminizing agent component in step 5 is: disperse aluminum powder in anhydrous ethanol at a weight ratio of 4:11, and ultrasonically disperse it at a frequency of 27 kHz for 7 minutes to obtain the aluminizing agent component.

[0083] The specific operation of the sintering treatment in step 5 is: first, heat infiltration at a temperature of 700° C. for 1 hour, and then tempering at a temperature of 500° C. for 2 hours.

[0084] Comparative Example 1

[0085] The manufacturing process of a NdFeB magnet provided in this comparative example is substantially the same as that in Example 1, the main difference being that in this comparative example 1, the main phase magnetic powder mixed with waste magnetic powder in Example 1 is replaced with main phase magnetic powder not mixed with waste magnetic powder.

[0086] Comparative Example 2

[0087] The manufacturing process of a NdFeB magnet provided in this comparative example is substantially the same as that in Example 1, with the main difference being that the step 5 in Example 1 is not performed in this comparative example 2, and the sintered blank prepared in this comparative example 2 is the NdFeB magnet.

[0088] Performance Testing

[0089] The NdFeB magnets prepared in Examples 1 to 3 and Comparative Examples 1 to 2 are marked as Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2, respectively. The performance of Examples 1 to 3 and Comparative Examples 1 to 2 is tested, and the obtained data are recorded in the following table:

[0090]

[0091] The corrosion potential and corrosion current density are obtained by first measuring the potentiodynamic polarization curve in a 3.5% by mass NaCl solution, and then fitting the corrosion potential and corrosion current density to the measured polarization curve using the Tafel extrapolation method.

[0092] It can be seen from the data shown in the above table that the density of the NdFeB magnets in Examples 1 to 3 is higher than that of the NdFeB magnets in Comparative Examples 1 to 2, and the intrinsic coercive force of the NdFeB magnets in Examples 1 to 3 is significantly higher than that of the NdFeB magnets in Comparative Examples 1 to 2; secondly, the corrosion current density of the NdFeB magnets in Examples 1 to 3 is lower, indicating that the NdFeB magnets in Examples 1 to 3 have better corrosion resistance and better magnetic properties. In summary, the manufacturing process of NdFeB magnets provided by the present invention has excellent market application prospects.

[0093] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0094] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A process for manufacturing NdFeB magnets, characterized in that: The manufacturing process comprises the following steps: Step 1: preparing a main phase component by mixing rare earth metal praseodymium-neodymium alloy, rare earth metal dysprosium-iron alloy, ferroboron, pure iron, ferroniobium, aluminum powder, pure gallium, pure copper and pure zirconium, wherein the main phase components are mixed in a weight ratio of 30:15:12:15:8:0.3:0.2:0.5:0.7; Step 2: After cleaning and drying the main phase components, hydrogen crushing and air flow milling are performed to prepare the main phase magnetic powder, and the NdFeB magnetic steel waste is recycled to prepare the waste magnetic powder; the specific operation of cleaning and drying the main phase components is: pouring the main phase components into dilute hydrochloric acid with a mass concentration of 5% and stirring and cleaning, stirring at a stirring speed of 100-200r / min for 1-2min, filtering and removing the filtrate, washing with distilled water for 3-5 times, and then drying under hot air at 35°C; Step 3: The main phase magnetic powder and the waste magnetic powder are mixed in a weight ratio of 3:1, and after mixing, they are subjected to magnetic field orientation pressing to form a green body. The orientation magnetic field conditions of the magnetic field orientation pressing are: the ambient oxygen content is less than 0.003% under argon protection, the orientation magnetic field is 2.0T, and the pressure is 5MPa. The pressing operation of the magnetic field orientation pressing in step 3 is: static pressing at a pressure of 200MPa to form a green body with a density of 6.5g / cm 2 of greenware; Step 4: placing the green body in a vacuum sintering furnace and sintering at 1030-1080° C. for 180 min, tempering at 850-920° C. for 150 min, and then tempering at 460-550° C. for 180 min, the result is recorded as a sintered body; Step 5: Mix aluminum powder and anhydrous ethanol to prepare an aluminizing agent component, and then evenly apply the aluminizing agent component on the surface of the sintered blank. After sintering, the resulting NdFeB magnet is obtained; the aluminizing agent component is prepared by dispersing aluminum powder in anhydrous ethanol at a weight ratio of 4:11, and ultrasonically dispersing it at a frequency of 25~28kHz for 5~8min to obtain the aluminizing agent component.

2. The manufacturing process of NdFeB magnet according to claim 1, characterized in that: The main phase components in step 1 are rare earth metal praseodymium-neodymium alloy with a purity of more than 99%, rare earth metal dysprosium-iron alloy with a purity of more than 99%, ferroboron with a purity of more than 99%, pure iron with a purity of more than 99%, ferroniobium with a purity of more than 99%, aluminum powder with a diameter of D5~D20mm, gallium with a purity of more than 99%, copper with a purity of more than 99% and zirconium with a purity of more than 99% mixed in proportion.

3. The manufacturing process of NdFeB magnet according to claim 1, characterized in that: The conditions for hydrogen crushing in step 2 are: hydrogen absorption pressure 220 kpa, hydrogen absorption time 2 h, dehydrogenation temperature 823 K, dehydrogenation time 6 h, the grinding gas pressure of the air flow mill process in step 2 is 0.45~0.6 MPa, and the powder particle size is 3.1~3.3 μm.

4. The manufacturing process of NdFeB magnet according to claim 1, characterized in that: The preparation steps of the waste magnetic powder in step 2 are: Step 1: Soak the NdFeB magnet scrap in trichloroethylene at 60°C for 5-6 minutes, then perform ultrasonic treatment at a frequency of 21-22kHz for 2-3 minutes and filter to remove trichloroethylene; Step 2: Soak the NdFeB magnet scrap treated in step 1 in a 20% hydrochloric acid solution and a 20% nitric acid solution in sequence, with a uniform soaking time of 20 seconds, filter out the filtrate and place in distilled water at 34-40°C, perform ultrasonic treatment at a frequency of 22-23kHz for 2-3 minutes, filter out the filtrate and blow dry with hot air at 38-40°C; Step 3: The NdFeB magnet scrap processed in step 2 is processed by hydrogen crushing and air flow grinding to obtain scrap magnetic powder.

5. The manufacturing process of NdFeB magnet according to claim 4, characterized in that: The conditions for hydrogen crushing in step three are: hydrogen absorption pressure 220 kpa, hydrogen absorption time 2 h, dehydrogenation temperature 823 K, dehydrogenation time 6 h, the grinding gas pressure of the air flow mill process in step three is 0.45~0.6 MPa, and the powder particle size is 2.8~3.1 μm.

6. The manufacturing process of NdFeB magnet according to claim 1, characterized in that: The two tempering treatments in step 4 are both below 5×10 -3 Pa under vacuum conditions.

7. The manufacturing process of NdFeB magnet according to claim 1, characterized in that: The specific operation of the sintering treatment in step 5 is: firstly heat infiltration at a temperature of 700° C. for 1 hour, and then tempering at a temperature of 500° C. for 2 hours.

Citation Information

Patent Citations

  • Low-manganese-content neodymium-iron-boron permanent magnet and manufacturing method

    CN104240887A

  • Method for making Nd-Fe-B series permanent magnet by using leftover bits and pieces of material

    CN1223182A